Protective activity of propofol, Diprivan® and intralipid against active oxygen species - M. Mathy-Hartert; G. Deby-Dupont; P. Hans; C. Deby; M. Lamy (Mediators of Inflammation)
We separately studied the antioxidant properties of propofol (PPF), Diprivan® (the commercial form of PPF) and intralipid (IL) (the vehicle solution of PPF in Diprivan® ) on active oxygen species produced by phorbol myristate acetate (10-6M)-stimulated human polymorphonuclear leukocytes (PMN: 5 × 10 5 cells/ assay), human endothelial cells (5 × 105 cells/assay) or cell-free systems (NaOCl or H2O2/peroxidase systems), using luminol (10-4M)-enhanced chemiluminescence (CL). We also studied the protective effects of Diprivan® on endothelial cells submitted to an oxidant stress induced by H2O2/MPO system: cytotoxicity was assessed by the release of preincorporated 51Cr. Propofol inhibited the CL produced by stimulated PMN in a dose dependent m anner (until 5 × 10-5 M, a clinically relevant concentration), while Diprivan® and IL were not dose-dependent inhibitors. The CL produced by endothelial cells was dosedependently inhibited by Diprivan® and PPF, and weakly by IL (not dose-dependent). In cell free systems, dose-dependent inhibitions were obtained for the three products with a lower effect for IL. Diprivan® efficaciously protected endothelial cells submitted to an oxidant stress, while IL was ineffective. By HPLC, we demonstrated that PPF was not incorporated into the cells. The drug thus acted by scavenging the active oxygen species released in the extracellular medium. IL acted in the same manner, but was a less powerful antioxidant.